2021
DOI: 10.20944/preprints202106.0333.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

2-Deoxy-d-glucose Inhibits Replication of Novel Coronavirus (SARS-CoV-2) with Adverse Effects on Host Cell Metabolism

Abstract: The treatment of viral infections is challenging owing to the intricate structure and metabolism of the viruses. In addition, they can highjack host cellular metabolism, mutate and adapt to harsh environmental conditions. The novel coronavirus (SARS-CoV-2) displays further resilient attributes, making its eradication even more difficult. SARS-CoV-2 is an enveloped virus whose replication can be targeted by limiting the substrates available for structural incorporation. One such molecule that limits substrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…So, inhibition of glucose uptake by GLUT4 could inhibit glucose transport and viral replication (Yu et al, 2011 ). In this regard, it has been hypothesized that activation of the PI3K/AKT signaling pathway by SARS‐CoV‐2 contributes to inducing glucose uptake through GLUT‐4 leading to increase glycolysis and viral replication in host cells (Malgotra & Sharma, 2021 ). Since it has been reported that genistein is a potent and direct inhibitor of GLUT‐4 (Lewicki et al, 2018 ), the direct inhibition of GLUT‐4 by genistein from one side and inhibition of the PI3K/AKT pathway from another side could disrupt the viral replication (Figure 2 ).…”
Section: Pharmacological Effects Of Genistein As a Probable Beneficia...mentioning
confidence: 99%
“…So, inhibition of glucose uptake by GLUT4 could inhibit glucose transport and viral replication (Yu et al, 2011 ). In this regard, it has been hypothesized that activation of the PI3K/AKT signaling pathway by SARS‐CoV‐2 contributes to inducing glucose uptake through GLUT‐4 leading to increase glycolysis and viral replication in host cells (Malgotra & Sharma, 2021 ). Since it has been reported that genistein is a potent and direct inhibitor of GLUT‐4 (Lewicki et al, 2018 ), the direct inhibition of GLUT‐4 by genistein from one side and inhibition of the PI3K/AKT pathway from another side could disrupt the viral replication (Figure 2 ).…”
Section: Pharmacological Effects Of Genistein As a Probable Beneficia...mentioning
confidence: 99%
“…As emergency medicine, doctors are relying on oxygen therapy, extracorporeal membrane oxygenation (ECMO), glucocorticoid supplementation (Dexamethasone), a common antibiotic, and antifungal treatments (van Paassen et al, 2020). Refer to Table 1 (Han et al, 2020;Madjid et al, 2020;Zheng, 2020;Ardestani and Azizi, 2021;Malgotra and Sharma, 2021;Shamsi et al, 2021).…”
Section: Treatments Availablementioning
confidence: 99%
“…So, besides its therapeutic use in seizures, cancer and, viral infections, clinical trials prove its efficient use in the treatment of COVID-19 helping the faster recovery of the hospitalized patients and reducing the dependence on supplemental oxygen. 2-DG is a non-selective and dose-dependent oral administrative drug that can cause several adverse effects on the heart, platelets, adrenal medulla, and neurons [91]. However, the reports showed that its cautious and prescribed use has resulted in the RT-PCR negative conversations in the COVID-19 patients (Figure 11).…”
Section: -Deoxy-d-glucosementioning
confidence: 99%